POTENSI PEMANFAATAN GAMBIR (Uncaria gambir Roxb) DI KECAMATAN PERGETTENG GETTENG SENGKUT, KABUPATEN PAKPAK BHARAT, PROVINSI SUMATERA UTARA - Jeckson Fransiskus Sagala; Rudi Hartono; Irawati Azhar (Peronema Forestry Science Journal, 2015)
Gambir (Uncaria gambir Roxb) is a kind of dried sap which is produced from leaves and twig of plant extract. Gambir is used traditionally for various purposes such as mixture of betel nut, drugs, adhesives and textile industry. One of central production of gambir in Indonesia is Pakpak Bharat District, North Sumatera Province. The purpose of this research were to getting information about technique of gambir processing in Sub-district of Pergetteng Getteng Sengkut and to comparing the quality of gambir with SNI 01-3391-2000. The method of this research was descriptive method using interview of respondent, then direct observation in field of gambir processing. The research showed that the technique of gambir processing generally was simple and used the traditional tools. The steps of gambir processing were boiling and compressing leaves, then the sap was got from compressed the leaves. After that, the sap was sedimented, drained to a paste form, and dried. The result of these research showed that the yield was 5.80% with the range from 5.26-6.04%. The moisture content of gambir from Simapera village was 15.38% and fulfilled the quality II, whereas the other villages in Sub-district Pergetteng Getteng Sengkut did not fulfill the quality requirements. Ash content and water-insoluble materials content were fulfilled the quality I and quality II.Keywords : Gambir, processing techniques, yield, moisture content, ash content, water-insoluble materials content